2012
DOI: 10.1257/mac.4.3.66
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Shocks and Economic Growth: Evidence from the Last Half Century

Abstract: This paper uses historical fluctuations in temperature within countries to identify its effects on aggregate economic outcomes. We find three primary results. First, higher temperatures substantially reduce economic growth in poor countries. Second, higher temperatures appear to reduce growth rates, not just the level of output. Third, higher temperatures have wide-ranging effects, reducing agricultural output, industrial output, and political stability. These findings inform debates over climate's role in eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
1,403
6
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,349 publications
(1,497 citation statements)
references
References 42 publications
78
1,403
6
10
Order By: Relevance
“…The authors argue that, while it is difficult to find a direct effect of climate variability on migration flows, as shown by [53], climate anomalies spur international migration by reducing the agricultural share in the economy. However, one shortcoming of the analysis carried out in this paper is that, by using the agricultural share in GDP as a mediating variable, one can hardly explain whether the effect of climate change works specifically through the agricultural channel or, more generally, through its impact on the overall economic condition of the country, as pointed out by [37]. In addition, the 2SLS gravity specification is quite far from the standards that are normally adopted in the trade literature.…”
Section: Macro-studies At the Country Levelmentioning
confidence: 86%
See 1 more Smart Citation
“…The authors argue that, while it is difficult to find a direct effect of climate variability on migration flows, as shown by [53], climate anomalies spur international migration by reducing the agricultural share in the economy. However, one shortcoming of the analysis carried out in this paper is that, by using the agricultural share in GDP as a mediating variable, one can hardly explain whether the effect of climate change works specifically through the agricultural channel or, more generally, through its impact on the overall economic condition of the country, as pointed out by [37]. In addition, the 2SLS gravity specification is quite far from the standards that are normally adopted in the trade literature.…”
Section: Macro-studies At the Country Levelmentioning
confidence: 86%
“…The relationship between weather variables (temperature and precipitation) and economic development, both in levels and in growth rates, has been analyzed by means of panel data methods in [35] and [36,37], where the authors found that the relationship between income and weather is significantly negative only in developing countries. It may be interesting to note that this relationship appears to be mainly driven by the negative effect of warming on agricultural output: an increase of 1 • C in average annual temperature translates to a 2.6 percentage point decrease in agricultural output.…”
Section: Panel Data Modelsmentioning
confidence: 99%
“…Burke and Emerick (2013) use this long-difference (LD) model for climate related study for US agriculture, while Dell et al (2012) apply it to economic growth analysis. Naturally, d does not have to be a decade; it could be longer or shorter, just as long as it is long enough to capture local climate from annual weather variation.…”
Section: Estimation Through Annual Weather Variation and Mid-term CLImentioning
confidence: 99%
“…For US agriculture, Burke and Emerick (2013) used five-year periods of 1978-1982 and 1998-2002. For climate versus economic growth with country level global data Dell et al (2012) use fifteen year averages of 1970-1985 and 1985-2000. Due to the limited data span available for Russia, we will use two non-overlapping periods of 1995-2001 and 2002-2009.…”
Section: Estimation Through Annual Weather Variation and Mid-term CLImentioning
confidence: 99%
See 1 more Smart Citation